Integrative taxonomy of the Pseudo-nitzschia (Bacillariophyceae) populations in the NW Adriatic Sea, with a focus on a novel cryptic species in the P. delicatissima species complex. Issue 3 (4th May 2021) - Giulietti, Sonia; Romagnoli, Tiziana; Siracusa, Melania; Bacchiocchi, Simone; Totti, Cecilia; Accoroni, Stefano
ABSTRACT: Species of the genus Pseudo-nitzschia are common inhabitants of phytoplankton communities of the northern Adriatic Sea, reaching high abundances. During 2018–2019, a total of 138 cultured Pseudo-nitzschia strains were isolated from northwestern Adriatic Sea and were characterized by using both morphological (TEM) and molecular (LSU, ITS, ITS2 secondary structure) approaches. Observation of frustule ultrastructure and phylogenetic analysis resolved a total of six taxa, i.e. P. fraudulenta, P. pungens, P. calliantha, P. mannii, P. delicatissima and P . cf. arenysensis . Results of the integrative taxonomic approach clearly revealed that P . cf. arenysensis is a cryptic species within P. delicatissima species complex. Pseudo-nitzschia cf. arenysensis is closely related to P. arenysensis, which forms a subclade and a sister group in LSU and ITS phylogenies, respectively. When comparing ITS2 secondary structure of P . cf. arenysensis and P. arenysensis, 1 CBC, 1 HCBC and 2 SNPs were recognized, suggesting reproductive isolation. Domoic acid production was not detected in any of the studied strains.